Selection of test bites records as part of a forensic bite mark analysis protocol - Fernando Rivera-Mendoza; Stella Martín-de-las-Heras; Pablo Navarro-Cáceres; Gabriel M. Fonseca (Egyptian Journal of Forensic Sciences, 2018)
Abstract Background Test bites have been recommended for collecting evidence of suspected dentition in bite mark analysis. However, these recommendations only suggest recording the interocclusal relationship without establishing number of records or characteristics to obtain proper records. This fails to consider not only the possibility that the recording material did not respond properly, but also that the evaluator has not detected simulations, habits or parafunctions that may affect the tests. Methods This research establishes differences between three wax test bites taken from the same subjects to determine if the first bite offered the best quality. Results No significant statistical association was found between the number of test bites recorded and respective quality. The interrater agreement produced almost perfect and substantial agreements. Conclusion There is no significant evidence that a first and only test bite is the highest quality test bite. Therefore, it is recommended to take more than a single bite test in controlled situations.